The L1Md long interspersed repeat family in the mouse: almost all examples are truncated at one end. - Voliva, C F (1983)
We have characterized a large repetitive element which has been found at seven different locations within the beta globin locus of the BALB/c mouse. This repeat has an unusual structure in that each of the different members has the same end of the element conserved while the other end terminates at a different point in each repeat member. The sequences within the repeats from the beta globin locus have homology with other repetitive families such as the MIF-1, Bam-5, R, and the BamH1 families. These were recently proposed (T. Fanning, (1983) Nucleic Acids Res. 11, 5073-5091) to be part of a structure with the same organization which we found in the globin locus. Probing plaques from a BALB/c genomic library with sequences derived from the repeats in the globin locus shows that virtually all of the repeats from this family are organized in a manner consistent with the proposed structure.